Hazardous chemicals handbook - Carson, P. A. (Phillip A.), 1944-; Mumford, C. J. (Oxford : Butterworth-Heinemann, 2002)
"Every health and safety practitioner should have a copy of this handbook as it is not simply of value to those working in the chemical and related industries, it is also of value to those studying for advanced health and safety qualifications." Safety & Health Practitioner The authors' aim with this handbook, is to provide a rapid ready-reference to help in the often complex task of handling, using and disposing of chemicals safely and with minimum risk to people's health or damage to facilities or to the environment. The book provides look-up data, and concise, clear explanations of general chemical principles, physiochemical and reactive properties, toxicities and exposure limits, flammability characteristics, monitoring techniques, personal protection and other parameters and requirements relating to compliance with designated safe practice, control of risks to people's health and limitation of environmental impact. Over 600 pages of valuable reference materialIncludes information on physiochemical and reactive properties, toxicities and exposure limits, flammability characteristics, monitoring techniques, personal protection and other parameters and requirements relating to complianceSummarizes core information for quick reference in the workplace or in transit.
Introduction; Terminology; Principles of Chemistry; Physicochemistry; Toxic Chemicals; Flammable Chemicals; Reactive Chemicals; Cryogens and other liquefied gases; Compressed gases; Monitoring Techniques; Radioactive Chemicals; Safety by design; Operating Procedures; Marketing; Transport of Chemicals; Chemicals and the Environment; Monitoring and Protection; Conversion Tables; Bibliography; Index.
Includes bibliographical references (p. [552]-592) and index.
Keywords: Hazardous substances -- Handbooks, manuals, etc; Hazardous Waste -- Analysis; Chemistry, Analytical; Environmental Monitoring -- Methods; Hazardous Substances -- Analysis; Safety Management; Electronic books; Handbooks, manuals, etc